2020
DOI: 10.1111/jfbc.13509
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobiumliquor eliminates free radicals and suppresses cellular proteins expression disorder to protect cells from oxidant damage

Abstract: Dendrobium liquor obtained by soaking Dendrobium in Chinese liquor is considered as a health drink in China. Here, we found the pretreatment of extract of Dendrobium nobile Lindl. liquor (DNLE) attenuated the oxidative damage to cells caused by H 2 O 2 , while the abilities of DNLE of eliminating extracellular free radicals and promoting the activities of intracellular antioxidant enzymes were observed. Quantitative proteomics identified 375 differentially expressed proteins caused by H 2 O 2 treatment in 293T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Aging is a complex and progressive biological process involving a wide range of chronic alterations in organs and tissues, including physiological and pathological changes, and is associated with multiple diseases, such as diabetes, cardiovascular disease, neurological diseases and cancer, and other geriatric syndromes [1][2][3][4]. The free radical oxidative stress (ROS) doctrine has become one of the most convincing theories of aging [5]. The accumulation of ROS under oxidative stress conditions leads to the induction of lipid peroxidation, resulting in advanced lipid oxidation end products (ALEs).…”
Section: Introductionmentioning
confidence: 99%
“…Aging is a complex and progressive biological process involving a wide range of chronic alterations in organs and tissues, including physiological and pathological changes, and is associated with multiple diseases, such as diabetes, cardiovascular disease, neurological diseases and cancer, and other geriatric syndromes [1][2][3][4]. The free radical oxidative stress (ROS) doctrine has become one of the most convincing theories of aging [5]. The accumulation of ROS under oxidative stress conditions leads to the induction of lipid peroxidation, resulting in advanced lipid oxidation end products (ALEs).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DNLE was also capable of mitigating the unfolded protein response and cell cycle disorder caused by oxidative stress. [42]…”
Section: Pharmacological Effects Of D Nobile and The Associated Molec...mentioning
confidence: 99%
“…Moreover, DNLE was also capable of mitigating the unfolded protein response and cell cycle disorder caused by oxidative stress. [42] Hypoglycemic effect Metabolic syndrome is a common chronic disease characterized by obesity, dyslipidemia, raised blood pressure, and high glucose levels. MS significantly augments the risk of type 2 diabetes and adversely affects human health.…”
Section: Anti-agingmentioning
confidence: 99%
“…Pharmacological research confirmed that D. nobile improves cognitive dysfunction, reduces gastric damage, has anti‐tumor effects, and can be used to treat diabetes 4 . Due to its beneficial effects, D. nobile is also used as a tonic and functional food, such as Dendrobii Liquor 5 . Broad applications increased the demand for D. nobile and hence resulted in a sharp decline of wild D. nobile populations.…”
Section: Introductionmentioning
confidence: 99%
“…4 Due to its beneficial effects, D. nobile is also used as a tonic and functional food, such as Dendrobii Liquor. 5 Broad applications increased the demand for D. nobile and hence resulted in a sharp decline of wild D. nobile populations. In the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) Appendix II, wild D. nobile is included.…”
Section: Introductionmentioning
confidence: 99%